Empowering School Communities: A Leadership Model for Improving Educational Quality in Resource-Constrained Areas - Shofwan Arif Ibrahim Arif; Rasiman Rasiman; Qristin Violinda (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes the implementation of diversification-based marketing strategies at Muhammadiyah Junior High School 8 Mijen Semarang to strengthen the institution's attractiveness and sustainability amidst the increasing competition in the private school sector. The research uses a qualitative case study approach with data triangulation through interviews, observations, and internal document reviews. The results show that although the school has developed flagship programs such as the Muhammadiyah Boarding School (MBS), the integration of the STEM curriculum, and bilingual classes supported by facilities such as national standard science laboratories and modern dormitories, the use of digital media for promotion is still very limited. A surprising finding emerged when the majority of prospective students learned about the school not through online media, but rather through word-of-mouth or by chance, indicating a systemic failure in the implementation of digital marketing strategies. Furthermore, the involvement of alumni and the community in school promotions is also minimal. The practical contribution of this research is the importance of transformation in school marketing management, including training the promotion team, integrating the use of big data into digital strategies, and activating alumni and community networks as promotional agents. This study confirms that excellent educational programs, without the support of an adaptive and optimal marketing system, will not be able to maximize their potential, causing the existing programs to remain relatively unknown and not maximally influencing prospective students' interest.